2009
DOI: 10.1016/j.ejim.2008.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Routine transthoracic echocardiography in a general Intensive Care Unit: An 18 month survey in 704 patients

Abstract: The authors analyzed 704 transthoracic echocardiographic (TTE) examinations, performed routinely to all admitted patients to a general 16-bed Intensive Care Unit (ICU) during an 18-month period. Data acquisition and prevalence of abnormalities of cardiac structures and function were assessed, as well as the new, previously unknown severe diagnoses.A TTE was performed within the first 24 h of admission on 704 consecutive patients, with a mean age of 61.5 ± 17.5 years, ICU stay of 10.6 ± 17.1 days, APACHE II 22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 24 publications
5
34
0
1
Order By: Relevance
“…10 In general, echocardiography has been shown to improve clinical diagnosis and patient management in the intensive care unit setting and emergency room, particularly in patients with cardiac dysfunction. 3,[11][12][13] Over the last decade, there has been an increasing use of echocardiography performed by neonatologists around the world. 14 In the year 2000, Evans 9 conducted a survey in Australia and New Zealand to establish the number of NICUs where neonatologists performed echocardiography; he found that 41% of NICUs had a neonatologist providing the primary echocardiography service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In general, echocardiography has been shown to improve clinical diagnosis and patient management in the intensive care unit setting and emergency room, particularly in patients with cardiac dysfunction. 3,[11][12][13] Over the last decade, there has been an increasing use of echocardiography performed by neonatologists around the world. 14 In the year 2000, Evans 9 conducted a survey in Australia and New Zealand to establish the number of NICUs where neonatologists performed echocardiography; he found that 41% of NICUs had a neonatologist providing the primary echocardiography service.…”
Section: Discussionmentioning
confidence: 99%
“…2 In adult intensive care units, use of trans-esophageal echocardiography is common practice and has been shown to change the clinical management in up to 30% of patients based on the results; in an additional 10% of patients it may detect severe previously unknown diagnoses. 3 There is some evidence that routine use of TnECHO in the neonatal unit may lead to identification of cardiovascular compromise, changes in management 4 and potentially improve short-term outcomes. 5 A TnECHO service was first introduced to the Hospital for Sick Children (HSC), Toronto in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Haemodynamic instability or shock is a recognised indication for both transoesophageal and transthoracic echocardiography in order to assess volume status, prediction of fluid responsiveness [41][42][43][44] and response to initiated therapy [21,[45][46][47]. In five transoesophageal echocardiography studies and one transthoracic echocardiography study, there were frequent changes in diagnosis of the haemodynamic status, however management changes were only reported in two of the transoesophageal echocardiography studies and none in the transthoracic echocardiography studies; this is an area that we believe deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Dies kann die Unterscheidung von einem akuten Koronarsyndrom als wichtige Differenzialdiagnose schwierig machen, welches eine unmittelbare andere therapeutische Intervention (Antikoagulation, Notfallrevaskularisation) erfordern würde. Die myokardiale Perfusionsechokardiographie kann helfen, diese beiden Diagnosen zu differenzieren, da die septische (und zirrhotische) Kardiomyopathie im Gegensatz zum akuten Koronararterienverschluss typischerweise eine normale Perfusion mit segmentaler Kinetikstörung zeigt [25].…”
Section: Kardiale Komplikationenunclassified